Discriminatory auctions with seller discretion: evidence from German treasury auctions - Jörg Rocholl (Deutsche Bundesbank, 2005)
This paper examines the results of 93 discriminatory German Treasury auctions between 1998 and 2002. It documents the seller's use of discretion and its influence on auction outcomes and bidding strategies. The evidence suggests that the seller uses its discretion frequently and substantially. It does not maximize revenues in a single-period game, but moves up in the competitive demand curve to set the auction price close to the market price. Bidders do not make profits in German auctions on average, while their bidding strategies reflect the uncertainty created by the seller's discretion. The paper extends and tests the multi-unit auction model by Lengwiler (1999). The empirical evidence is consistent with the implication that the market-clearing price depends on the seller's marginal cost rather than on the submitted demand.
Keywords: H63; G28; 330; Discriminatory auctions; Winner's curse; Seller discretion; Schatzpapier; Öffentliche Anleihe; Wertpapieremission; Auktionstheorie; Wiederholte Spiele; Schätzung; Deutschland